Reform Chatter and Democracy - Arezki, Rabah; Djankov, Simeon; Nguyen, Ha; Yotzov, Ivan (World Bank, Washington, DC, 2020)
This paper explores the dynamics of media chatter about economic reforms using text analysis from about a billion newspaper articles in 28 languages. The paper shows that the intensity of reform chatter increases during economic downturns. This increase is more significant in democracies. Using instrumental variable techniques, the analysis finds the relationship to be causal. The paper also documents that reform chatter is followed by actual reforms, suggesting that democracies benefit from a "self-correcting" mechanism stemming from changing popular attitudes toward reform.